Effect of Exogenous of Transforming Growth Factor-β1 on Pregnancy Outcome in Mice with Recurrent Pregnancy Loss by Persistent Enhancement of Placental Tissue Indoleamine 2,3-Dioxygenase Expression - Xinghui Wen; Xiaojuan Chen; Mei Li; Jinnian Zhou; Shouli Dao; Shixiang Li; Hui Cheng; Shuyun Zhao; Guanyou Huang (International Journal of Fertility and Sterility)
Background: The immunologic factors are the chief reason for recurrent pregnancy loss (RPL) and induction ofmaternal-fetal tolerance is the main treatment for this cause of RPL, but the effect of this method is uncertainly andneeds multiple doses and/or interventions. The aim of this study was to investigate whether a single administrationof transforming growth factor-β1 (TGF-β1) can improve the pregnancy outcomes of RPL mice and whether theimprovement is cause by TGF-β1 driving the expression of immune tolerance molecule indoleamine 2,3-dioxygenase(IDO).Materials and Methods: In this experimental study, 40 RPL model mice were equally divided into a control group,that received 0.01 M phosphate-buffered saline (PBS), and a treatment group, that received PBS containing 2, 20, and200 ng/ml TGF-β1 via tail vein injection. The mice were sacrificed at 13.5 days of pregnancy and the embryo resorptionrate was determined. The expression of IDO, TGF-β1, and TGF-β3 were detected in the placenta using westernblotting and immunohistochemistry techniques.Results: The expression of IDO was positively correlated with TGF-β1 in the placental tissue of RPL mice (r=0.591,P<0.001). In all treatment groups, the embryo resorption rates were significantly lower than the control group andthe expression of IDO in the placental tissue of all treatment groups was significantly higher than the control group.The expression of TGF-β1 increased gradually from, 2, 20 to 200 ng/ml in treatment groups, and the concentrationof exogenous TGF-β1 positively correlated with the expression of TGF-β1, in placental tissues in treatment groups(r=0.372, P=0.018).Conclusion: Exogenous TGF-β1 improves pregnancy outcomes in RPL mice, and the possible therapeutic mechanismis that exogenous TGF-β1 induces the persistent expression of endogenous TGF-β1 and IDO due to mutuallyinduced expression of the other. This experiment may provide a new direction and idea for the future treatment ofRPL patients.